STRATEGI GURU PAI DALAM MENGATASI GANGGUAN FOKUS BELAJAR PESERTA DIDIK KELAS VII DI SMPIT AL-RIDWAN KARAWANG - Zahrah, Windy Athira; Taufik Mustofa; Nia Karnia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the learning focus disturbances experienced by seventh-grade students at SMPIT Al-Ridwan Karawang, which may affect the effectiveness of the Islamic Religious Education (PAI) learning process. Learning focus disturbances cause students to become less attentive during lessons, easily distracted, and less actively involved in learning activities. This study aimed to identify the strategies employed by Islamic Religious Education teachers in addressing students' learning focus disturbances, the supporting and inhibiting factors affecting the implementation of these strategies, and the outcomes of their implementation. This study employed a qualitative approach using a case study method. The research informants consisted of the principal, an Islamic Religious Education teacher, and seventh-grade students at SMPIT Al-Ridwan Karawang. Data were collected through observation, interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings revealed that the teachers' strategies in addressing learning focus disturbances were implemented through learning planning, implementation, and evaluation. Supporting factors included adequate learning facilities, a conducive school environment, effective school management, interactive learning activities, school support for Islamic Religious Education, and continuous monitoring of teaching and learning activities. Inhibiting factors included limited facilities and infrastructure, peer distractions, and differences in students' learning motivation and focus. The implementation of these strategies was able to improve students' attention, participation, understanding of learning materials, task completion, and retention of learning content.